Equilibrium disorders in workers exposed to mixed solvents. Issue 4 (2nd October 2019) - Giorgianni, Concetto; Tanzariello, Mariagiuseppina; De Pasquale, Domenico; Brecciaroli, Renato; Spatari, Giovanna
Abstract : Background . Organic solvents cause diseases of the vestibular system. However, little is known regarding the correlation between vestibular damage and exposure to organic solvents below threshold limit values. The best measure by which to evaluate vestibular disorders is static and dynamic posturography. Objective . The aim of this study was to evaluate equilibrium disorders via static and dynamic posturography in workers without clear symptoms and exposed to low doses of mixed solvents. Methods . 200 subjects were selected . Using an Otometrics device (Madsen, Denmark), all subjects endured static and dynamic posturography testing with both eyes-open and eyes-closed conditions. Results were compared with a control group of unexposed individuals. Result . Based on the obtained data, the following results can be drawn: (a) subjects exposed to mixtures of solvents show highly significant differences regarding all static and dynamic posturography parameters in comparison to the control group; (b) posturography testing has proven to be a valid means by which to detect subliminal equilibrium disorders in subjects exposed to solvents. Conclusion . We can confirm that refinery workers exposed to mixtures of solvents can present subliminal equilibrium disorders. Early diagnosis of the latter is made possible by static and dynamic posturography.